The APOA5 Trp19 allele is associated with metabolic syndrome via its association with plasma triglycerides - Ferrières Jean; Bingham Annie; Arveiler Dominique; Ruidavets Jean-Bernard; Ducimetière Pierre; Wagner Aline; Cottel Dominique; Dallongeville Jean; Amouyel Philippe; Meirhaeghe Aline (BMC Medical Genetics, 2008)
Abstract Background The goal of the present study was to assess the effect of genetic variability at the APOA5/A4/C3/A1 cluster locus on the risk of metabolic syndrome. Methods The APOA5 Ser19Trp, APOA5 -12,238T>C, APOA4 Thr347Ser, APOC3 -482C>T and APOC3 3238C>G (SstI) polymorphisms were analyzed in a representative population sample of 3138 men and women from France, including 932 individuals with metabolic syndrome and 2206 without metabolic syndrome, as defined by the NCEP criteria. Results Compared with homozygotes for the common allele, the odds ratio (OR) [95% CI] for metabolic syndrome was 1.30 [1.03–1.66] (p = 0.03) for APOA5 Trp19 carriers, 0.81 [0.69–0.95] (p = 0.01) for APOA5 -12,238C carriers and 0.84 [0.70–0.99] (p = 0.04) for APOA4 Ser347 carriers. Adjustment for plasma triglycerides, (but not for waist girth, HDL, blood pressure or glycemia – the other components of metabolic syndrome) abolished these associations and suggests that triglyceride levels explain the association with metabolic syndrome. There was no association between the APOC3 -482C>T or APOC3 3238C>G polymorphisms and metabolic syndrome. The decreased risk of metabolic syndrome observed in APOA5 -12,238C and APOA4 Ser347 carriers merely reflected the fact that the APOA5 Trp19 allele was in negative linkage disequilibrium with the common alleles of APOA5 -12,238T>C and APOA4 Thr347Ser polymorphisms. Conclusion The APOA5 Trp19 allele increased susceptibility to metabolic syndrome via its impact on plasma triglyceride levels.